2012
DOI: 10.1371/journal.pone.0044091
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogonial Stem Cell Markers and Niche in Equids

Abstract: Spermatogonial stem cells (SSCs) are the foundation of spermatogenesis and are located in a highly dynamic microenvironment called “niche” that influences all aspects of stem cell function, including homing, self-renewal and differentiation. Several studies have recently identified specific proteins that regulate the fate of SSCs. These studies also aimed at identifying surface markers that would facilitate the isolation of these cells in different vertebrate species. The present study is the first to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 70 publications
4
40
0
2
Order By: Relevance
“…Tissue expression studies have shown that PLZF is expressed in testis of different species such as the carp (Mohapatra et al 2010) and the mouse (Kokkinaki et al 2010), as observed in the dogfish, even if its expression was higher in the liver and eye than in the testis. In dogfish, plzf was detected not only in undifferentiated spermatogonia, in agreement with observations in various mammals and in zebrafish (Hermann et al 2009, Kokkinaki et al 2010, Ozaki et al 2011, Costa et al 2012, but also in differentiated spermatogonia, a larger expression pattern also described in humans and monkeys (Hermann et al 2009). Surprisingly, plzf expression in dogfish meiotic germ cells and young spermatids was a unique case in the studied species.…”
Section: Pou2/pou5f1 and Gfra1 Are Highly Conserved Sscs Markerssupporting
confidence: 89%
See 2 more Smart Citations
“…Tissue expression studies have shown that PLZF is expressed in testis of different species such as the carp (Mohapatra et al 2010) and the mouse (Kokkinaki et al 2010), as observed in the dogfish, even if its expression was higher in the liver and eye than in the testis. In dogfish, plzf was detected not only in undifferentiated spermatogonia, in agreement with observations in various mammals and in zebrafish (Hermann et al 2009, Kokkinaki et al 2010, Ozaki et al 2011, Costa et al 2012, but also in differentiated spermatogonia, a larger expression pattern also described in humans and monkeys (Hermann et al 2009). Surprisingly, plzf expression in dogfish meiotic germ cells and young spermatids was a unique case in the studied species.…”
Section: Pou2/pou5f1 and Gfra1 Are Highly Conserved Sscs Markerssupporting
confidence: 89%
“…As the highest expression level of gfra1 was found in dogfish brain, we can hypothesize a similar function in S. canicula. In testis cells, GFRa1 was reported to be a marker of undifferentiated spermatogonia in many mammalian models (Suzuki et al 2009, Costa et al 2012. GFRa1 and its co-receptor RET stimulate SSC self-renewal in response to the GDNF (Naughton et al 2005).…”
Section: Pou2/pou5f1 and Gfra1 Are Highly Conserved Sscs Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the GFRα1 (GDNF Family Receptor α1) has been described as a marker of undifferentiated spermatogonia in mouse [7], equids [8], buffalo [9] or collared peccary [10] and more recently in fishes such as the Nile tilapia [5]. Other undifferentiated spermatogonial markers were identified in various species such as the cell surface marker Thy1 (Thymus cell antigen 1) in mouse [11], bull [12] and carp [13] or the following transcriptional factors: PLZF (Promyelocytic Leukaemia Zinc Finger protein) in mouse [7], equids [8] and zebrafish [14], POU2/POU5F1 in mouse [15], buffalo [9] and carp [13] and ID4 (Inhibitor of DNA binding 4), a more selective marker of SSCs than Thy1, in the mouse [16]. Some of these defined markers were used to improve in vitro culture systems by selecting undifferentiated spermatogonia from the testicular cell population, including potential SSCs, using the MACS technology (Magnetic-Activated Cell Sorting) in mammals as well as in Teleosts.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, promyelocytic leukemia zinc-finger protein (PLZF, also known as ZBTB16), a transcription factor essential for the maintenance and self-renewal of SSCs, is initially found to be expressed by mouse undifferentiated spermatogonia (Buaas et al 2004, Costoya et al 2004. Later, its expression in a sub-population of gonocytes and SSCs/progenitors in pigs, cattle, sheep, goats, and equids is verified (Luo et al 2006, Borjigin et al 2010, Reding et al 2010, Costa et al 2012, Zheng et al 2013a.…”
Section: Characterization Of Spermatogonia In Domestic Animalsmentioning
confidence: 99%